A pilot randomized control trial on the feasibility, acceptability, and initial effects of a digital-assisted parenting intervention for promoting mental health in Malaysian adolescents - Zulkefly, Nor Sheereen; Dzeidee Schaff, Anis Raihan; Zaini, Nur Arfah; Mukhtar, Firdaus; Dahlan, Rahima (SAGE Publications Inc., 2024)
Objective: Online parenting interventions for enhancing child development, specifically mental health is relatively new in Malaysia. This pilot study tests the feasibility, acceptability, and initial effects of a universal digital-assisted parenting intervention (DaPI) in promoting mental health in adolescents by improving parental behaviors and self-efficacy. Methods: A two-arm pilot randomized controlled trial was conducted. Twenty-four mothers of adolescent aged 10 to 14 years from a non-clinical sample were recruited online and randomly allocated into two groups (intervention [DaPI] and waitlist-control [WLC]). Eight weekly sessions were delivered online via technological devices. Feasibility outcomes were based on the participants’ engagement in DaPI and study retention. Primary (parental behaviors and self-efficacy) and secondary (adolescent mental health) outcomes were assessed using an online survey at baseline (T0), post-intervention (T1), and 1-month follow-up (T2). Data were analyzed using descriptive and inferential statistics and an intention-to-treat approach. Results: The DaPI was well received by the mothers. Retention was high (81.8%) in both groups and intervention adherence was excellent (91.6%). Within-group analyses showed a significant decrease in physical control at T2 and an increase in parental self-efficacy at T1 and T2 among the DaPI mothers. No significant differences were observed in adolescents’ mental health at any time point. As for the WLC group, there were no significant differences in all the outcome variables across the three assessment moments. Between groups analyses revealed DaPI mothers had significant differences in proactive parenting at T1, and in positive reinforcement and lax control at T2. There were no significant differences in adolescents’ mental health between the groups at any time point. Discussion: The DaPI is feasible and acceptable in the Malaysian context. Findings show promise regarding the initial effects of the DaPI. However, a larger RCT is needed to determine its effectiveness in promoting mental health of adolescents.